Climate change affects wetland resources in Bangladesh: A case study on Hakaluki Haor / Mohd Shahadat Hossain - Hossain, Mohd Shahadat (Research Management Institute (RMI), 2013)
The wetlands of Bangladesh support a wide variety of floral and faunal diversity. Approximately half the area of the country can be considered as wetlands consisting of a wide variety of types ranging from haors, beels, lakes, rivers and coastal forests to deepwater paddy fields and ponds. The wetland resources of Bangladesh are of enormous economic importance. The present study has attempted to observe the present situation of existing condition of wetland resources. However these aquatic resources have been subjected to rapid degradation due to the increasing population pressure, habitat destruction as well as natural causes. Hakaluki haor is one of the major wetlands of Bangladesh. With a land area of 18,386 hectares, it supports a rich biodiversity and provides direct and indirect livelihood benefits to nearly 190,000 people. Because of the critical conditions of the haor ecology, the government of Bangladesh declared Hakaluki as an Ecologically Critical Area (ECA) in April 1999.So the Hakaluki haor area is very important site for study as wetlands conservation practice. As there are some problems in conservation process, it is very important to try and find out the main causes of wetlands degradation and keep wetlands free from such harmful impacts. The study was initiated to find out the problems and propose some suggestions to develop the wetlands conservation process. The resources users were empowered with a collective effort to build institutions and implement sustainable use practices resulting in wetland resilience of the resources.